2007
DOI: 10.1002/path.2077
|View full text |Cite
|
Sign up to set email alerts
|

The ageing male reproductive tract

Abstract: Ageing of the male reproductive system is characterized by changes in the endocrine system, hypogonadism, erectile dysfunction and proliferative disorders of the prostate gland. Stochastic damage accumulating within ageing leads to progressive dysregulation at each level of the hypothalamic-pituitary-gonadal (HPG) axis and in local auto/paracrine interactions, thereby inducing morphological changes in reproductive target organs, such as the prostate, testis and penis. Despite age-related changes in the HPG axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 189 publications
(207 reference statements)
1
63
0
8
Order By: Relevance
“…Prostate enlargement in older men is one of the most common age-related diseases and is defined as benign prostatic hyperplasia (BPH). Although any DNA mutation associated with BPH has not been reported to date, in general DNA methylation has been shown to decrease in BPH [15,16]. Prakash et al have identified 511 differentially expressed genes that can distinguish symptomatic BPH from asymptomatic BPH and most of these genes encode epithelium/stroma-derived growth factors [17].…”
Section: The Effect Of Aging On Sexual Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate enlargement in older men is one of the most common age-related diseases and is defined as benign prostatic hyperplasia (BPH). Although any DNA mutation associated with BPH has not been reported to date, in general DNA methylation has been shown to decrease in BPH [15,16]. Prakash et al have identified 511 differentially expressed genes that can distinguish symptomatic BPH from asymptomatic BPH and most of these genes encode epithelium/stroma-derived growth factors [17].…”
Section: The Effect Of Aging On Sexual Organsmentioning
confidence: 99%
“…Premalignant dysplastic lesions (prostatic intraepithelial neoplasia, PIN) are characterized by enlarged nuclei, decline in basal epithelial layer, and proliferation and abnormal differentiation of secretory cells. PIN is regarded as pre-invasive stage of prostatic adenocarcinoma [16,19].…”
Section: The Effect Of Aging On Sexual Organsmentioning
confidence: 99%
“…12 The manifestations include decreased bone and muscle mass, sexual body hair and beard growth, and increased abdominal obesity, as well as higher incidence of erectile dysfunction, which increases to .30%-40% in the eighth decade. 7,12,13 Age-related erectile dysfunction has also been associated with endothelial dysfunction due to atherosclerosis of the penile arteries and a reduction in the production of nitric oxide. 7 In a retrospective study of 3698 infertile patients, the incidence of infection in the accessory glands increased from 6.1% among males aged ,25 years to 13.6% of patients aged .40 years, and total sperm count was lower (P,0.0001).…”
Section: Testicular Function and Spermatogenesismentioning
confidence: 99%
“…7,12,13 Age-related erectile dysfunction has also been associated with endothelial dysfunction due to atherosclerosis of the penile arteries and a reduction in the production of nitric oxide. 7 In a retrospective study of 3698 infertile patients, the incidence of infection in the accessory glands increased from 6.1% among males aged ,25 years to 13.6% of patients aged .40 years, and total sperm count was lower (P,0.0001). 14 Numerous studies have examined the age-related effect on semen characteristics.…”
Section: Testicular Function and Spermatogenesismentioning
confidence: 99%
See 1 more Smart Citation